Chemical synthesis of metal nanoparticles in aqueous solutions with the presence of some additives - Munetaka Oyama,; Akrajas Ali Umar,; Muhamad Mat Salleh,; Burhanuddin Yeop Majlis, (Universiti Kebangsaan Malaysia, 2011)
Metal nanoparticles having interesting shapes can be prepared in aqueous solutions through simple reductions of metal ions with the presence of some additive reagents, such as cetyltrimethylammonium bromide and hexamethylenetetramine. In this review, some successful results for shape-controlled synthesis of metal nanoparticles in our group are summarized, which includes the synthesis of palladium nanocubes, palladium nanobricks, gold nanotripods. In addition, combining with indium tin oxide electrode surfaces, shape-controlled growth is shown to be possible to form gold nanoplates and copper oxide nanowires. Even in relatively mild synthetic conditions, interesting shape-controlled synthesis of metal nanoparticles is possible.